THE CONCEPT OF SANOGENIC THINKING IN THE HISTORICAL AND SCIENTIFIC RETROSPECTIVE OF PSYCHOLOGICAL SCIENCE (Psychology Travelogs, 2025)
The article presents a historical and scientific analysis of the evolution of the concept of sanogenic thinking in the context of psychological science of the XX-XXI centuries. The research covers key theoretical studies, in particular cognitive, humanistic and positive directions, which laid the foundation for understanding sanogenic thinking as a tool for supporting mental health. The contribution of leading scientists is emphasized: A. Beck, A. Ellis, M. Seligman, A. Gilman, as well as the concept of A. Antonovsky's salutogenic approach, which defined sanogenic thinking as an integrative phenomenon that combines rational-cognitive, emotional-regulatory, and personal-value components. Sanogenic thinking is viewed as a system aimed at maintaining psycho-emotional balance, reducing stress and optimizing adaptation to life challenges. In contrast to positive thinking, which focuses on optimism, sanogenic thinking involves constructive work with negative emotions through self-reflection, cognitive restructuring, and management of internal resources. Particular attention is paid to the development of the concept in Ukrainian science, in particular to the works of O. Osadko, T. Kyrylenko, and A. Gilman, who expanded the content of sanogenic thinking by adding dialogic intentions, sanogenic reflection, and emphasizing social adaptation. The role of sanogenic thinking in the formation of stress resistance, prevention of psychosomatic disorders and support of mental health in the context of modern challenges, including social crises and war, is emphasized. The concept of sanogenic thinking is considered as an integrative category that combines rational-cognitive, emotional-regulatory and personal-value components that contribute to mental self-regulation and preservation of mental health under stress. The stages of the evolution of ideas about sanogenic thinking are identified and the scientific achievements that have become the methodological basis for the modern understanding of this type of thinking in psychology are characterized. The attention is focused on the humanistic and anthropocentric paradigm of thinking. The article proves that sanogenic thinking is an important object of scientific analysis in both theoretical and applied dimensions, in particular in the context of psychological prevention, psychotherapy and mental development of the individual.
Keywords: sanogenic thinking; positive thinking; psychological science; cognitive processes; mental health